11. Blood Chemistry of Local Swamp Buffaloes (Bubalus bubalis) of Aceh - Zoerul Fahlevi; Al Azhar; Arman Sayuti; M Isa; Mulyadi Adam; Herrialfian Herrialfian (Universitas Syiah Kuala, 2017)
This study was done to determine blood chemistry of local swamp buffaloes in Aceh. Blood samples were collected from 15 local buffaloes slaughtered at the abattoir of Banda Aceh and 16 local buffaloes slaughtered at the abattoir of Aceh Besar using EDTA as an anticoagulant. Measurement of uric acid, cholesterol and glucose levels was done using Easy Touch rapid test whereas hemoglobin concentration was determined using Sahli method. Data obtained was analyzed by t-test using GraphPad Prims 6 software. The results showed that concentration of uric acid, cholesterol, glucose and hemoglobin in the blood of local swamp buffaloes were 13.80±3.62 mg/dl, 139.50±39.71 mg/dl, 81.81±21.34 mg/dl, and 10.86±2.78 g/dl, respectively. In the male local buffaloes, the level of uric acid, cholesterol, glucose and Hb were 12.23±3.94 mg/dl, 126.10±33.99 mg/dl, 73.58±22.54 mg/dl, and Hb 11.20±3.86 g/dl, respectively. For female local buffaloes, uric acid level was 14.59±3.29 mg/dl, cholesterol was 147.70±41.61 mg/dl, glucose was 87.00±19.35 mg/dl, and Hb was 10.64±1.91 g/dl. Statistical analysis indicated that there was no difference in the chemistry profiles in the blood of local swamp buffaloes of Aceh according to sex.